Impact of biochar on soil N2O emissions under different biochar-carbon/fertilizer-nitrogen ratios at a constant moisture condition on a silt loam soil - Feng, Zhengjun; Zhu, Lizhong (The Science of the total environment, 2017)
Biochar amendment has been proposed as a potential solution for improving soil quality and suppressing greenhouse gas emission. Considering the serious nitrogen fertilizer overuse problem in China, it is important to investigate the effect of biochar on soil with excess nitrogen fertilizer. Therefore, two sets of soil column experiments were conducted to explore the effect of biochar on N2O emission from nitrogen fertilizer-overused soil. Three types of biochar (biochars pyrolzed at 300, 500 and 700°C, respectively) and one type of nitrogen fertilizer (ammonium sulfate) were investigated at varying application rates. It was found that N2O emission was related to both biochar and N-fertilizer application rates, and increased N2O emission was negatively correlated with the TC/IN ratio (the ratio of total carbon to inorganic nitrogen) after biochar application. The soil TC/IN ratio determined the ammonium utilization pathway, affecting the intensity of nitrification and N2O emission. When the TC/IN ratio was relatively high (>60), suppressed nitrification led to the suppression of N2O emission. Conversely, enhanced nitrification when the TC/IN ratio was relatively low (<45) caused the promotion of N2O emission. In conclusion, biochar's suppression of soil N2O emission was conditional and biochar should be applied in a proper ratio to nitrogen fertilizer to avoid excessive N2O emission. [Display omitted] •Soil N2O emission was affected by the ratio of biochar to N fertilizer.•When the ratio of biochar to N fertilizer was high, biochar suppressed N2O emission.•When the ratio of biochar to N fertilizer was low, biochar promoted N2O emission.•Biochar should be applied in proper ratio to N fertilizer to reduce N2O emission.